Hardy-Sobolev Type Inequality and Supercritical Extremal Problem - Ubilla-Lopez, P (American Institute of Mathematical Sciences, 2019)
This paper deals with Hardy-Sobolev type inequalities involving variable exponents. Our approach also enables us to prove existence results for a wide class of quasilinear elliptic equations with supercritical power-type nonlinearity with variable exponent. © 2019 American Institute of Mathematical Sciences. All Rights Reserved.